2023
DOI: 10.1002/ctm2.1318
|View full text |Cite
|
Sign up to set email alerts
|

ALKBH5/YTHDF2‐mediated m6A modification of circAFF2 enhances radiosensitivity of colorectal cancer by inhibiting Cullin neddylation

Abstract: The expression of circAFF2 is regulated by ALKBH5-mediated demethylation, and YTHDF2 mainly mediates its degradation in an m6A-dependent manner. CircAFF2 enhanced the radiosensitivity of CRC cells by binding to CAND1 and promoting the interaction of CAND1 with Cullin1, thereby inhibiting neddylation modification in CRC cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 47 publications
(149 reference statements)
0
3
0
Order By: Relevance
“…It has been shown that circRNAs containing m6A residues can be translated into protein by non-cap-dependent structures [26]. m6Amodified circRNA might be recognized by the YTHDF2 [27], in which the open reading framework (ORF) may be verified for the translational capability of the circRNA. Several effects of the peptide/protein from circRNA translation have been identified [28].…”
Section: Association Of M6a and Ncrnas With Various Liver Diseasesmentioning
confidence: 99%
“…It has been shown that circRNAs containing m6A residues can be translated into protein by non-cap-dependent structures [26]. m6Amodified circRNA might be recognized by the YTHDF2 [27], in which the open reading framework (ORF) may be verified for the translational capability of the circRNA. Several effects of the peptide/protein from circRNA translation have been identified [28].…”
Section: Association Of M6a and Ncrnas With Various Liver Diseasesmentioning
confidence: 99%
“…m 6 A methylation can be induced by radiotherapy. Shao and colleagues reported that IR (4 Gy) significantly increased the m 6 A levels in several colorectal cancer cells, probably due to the reduced m 6 A eraser ALKBH5 after IR ( Shao et al, 2023 ). A recent report noted that IR increases m 6 A reader YTHDF2 in MDSCs both in vitro (4 Gy) and in vivo (one dose of 20 Gy) ( Wang et al, 2022 , 2023a ).…”
Section: The Crucial Signaling Pathways Activated By Ir or Ir+immune ...mentioning
confidence: 99%
“…MLN4924 emerges as a novel radiosensitizer, augmenting the sensitivity of CRC to radiotherapy ( 53 ). In addition, the interaction between circAFF2 and cullin-associated and neddylation-dissociated protein 1 (CAND1) facilitates the binding of CAND1 to cullin5, suppressing cullin5 neddylation and consequently enhancing radiosensitivity in CRC ( 54 ).…”
Section: Overview Of Neddylationmentioning
confidence: 99%